New in a diagnosis and treatment of chronic endometritis at infertility - Klara G Serebrennikova; Igor I Babichenko; Narina A Arutyunyan; Sergey N Katsalap; Albina S Akateva (IP Berlin A.V., 2019)
Background. Chronic endometritis is one of the causes of infertility, miscarriage, failed in vitro fertilization and embryo transfer attempts. Treatment of chronic endometritis is quite complicated due to a multifactorial nature of endometrium morpho-functional disorders. There are lots of approaches to a comprehensive treatment of chronic endometritis which indicates a lack of a single algorithm for a management of such patients to date. One of the modern, perspective and high-tech methods for treatment of chronic endometritis is photodynamic therapy (PDT). Aim. To study chronic endometritis treatment efficacy in patients with infertility when using the method of PDT and low doses of 17b-estradiol. Materials and methods. 85 female patients of reproductive age with chronic endometritis were examined and treated. All patients were divided into 2 groups: group 1 (43 patients) got treated by a method of intravenous PDT with low-dose transdermal 17b-estradiol; group 2 (42 patients) received low-dose transdermal therapy with 17b-estradiol. Clinical examination and laboratory tests, pelvic ultrasound, endometrial aspiration biopsy followed by pathomorphlogical and immunohistochemical examination were carried out to all patient. Results. Ultrasound examination revealed an increase in endometrium thickness at 12th day following PDT session in group 1 and following transdermal therapy with 17b-estradiol in group 2 resulting in endometrium state improvement almost 2 times compared with baseline values before treatment. Conclusions. PDT is a minimally invasive, gentle and safe treatment method. Due to a diffuser design laser radiation is evenly distributed in the uterine cavity. PDT reliably restores receptor function to progesterone in the endometrial glands.